2019
DOI: 10.1139/cjpp-2018-0574
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of hydrogen sulfide decreased the progression of gonarthrosis

Abstract: Hydrogen sulfide (H2S) is found in both the plasma and synovial fluid of patients with gonarthrosis. In the present study, we investigated whether intra-articular injection of sodium hydrosulfide (NaSH) (1 mM, 30 μL), a H2S donor, might affect gonarthrosis in rats. Gonarthrosis was induced surgically in the left knees of rats and left for 6 weeks for the development of disease. Then, intra-articular injections of NaSH or methylprednisolone (1 mg/kg, 30 μL) were administered to rats. Half of each group was sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…We observed that intraarticular GYY-4137 administration protected cartilage against deterioration induced by the OA model. Previous studies support these findings [ 26 , 28 , 34 ]. For instance, the intra-articular injection of sodium hydrosulfide (NaSH), a fast-releasing H 2 S donor, slowed the development of degenerative changes in the articular cartilage in a model of gonarthrosis [ 26 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We observed that intraarticular GYY-4137 administration protected cartilage against deterioration induced by the OA model. Previous studies support these findings [ 26 , 28 , 34 ]. For instance, the intra-articular injection of sodium hydrosulfide (NaSH), a fast-releasing H 2 S donor, slowed the development of degenerative changes in the articular cartilage in a model of gonarthrosis [ 26 ].…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies support these findings [ 26 , 28 , 34 ]. For instance, the intra-articular injection of sodium hydrosulfide (NaSH), a fast-releasing H 2 S donor, slowed the development of degenerative changes in the articular cartilage in a model of gonarthrosis [ 26 ]. Likewise, cartilage damage as well as proteoglycan loss were exacerbated in 3-MST KO joints compared to WT joints in an experimental OA in mice [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Numerous findings have demonstrated the beneficial anti-inflammatory and protective actions induced by the exogenous administration of H 2 S in the cartilage and chondrocytes in cell cultures [32,33]. Other works have also proven the positive effects of the intra-articular administration of H 2 S donors on rheumatic disease progression [34], cartilage destruction, and oxidative damage in rats [35]. The antinociceptive and antidepressant effects of the systemic administration of H 2 S donors, such as isothiocyanates, in mice with knee osteoarthritis have also been shown [2,36].…”
Section: Introductionmentioning
confidence: 96%
“…All operations were carried out under sterile conditions in the specific pathogen-free animal center. Firstly, the animals were randomly assigned into the following six groups to examine the efficiency of transfection (n=3): i) The control group [injection of the same volume of the vehicle control (PBS) into knee joints] ( 19 , 20 ); ii) shRNA-NC group (injection of shRNA-NC into knee joints); iii) shRNA-XIST-1 group (injection of shRNA-XIST-1 into knee joints); iv) shRNA-XIST-2 group (injection of shRNA-XIST-2 into knee joints); v) OverExp-NC group (injection of overexpression-NC plasmids into knee joints); and vi) OverExp-XIST group (injection of overexpression-XIST plasmids into knee joints). Subsequently, the animals (different rats) were randomly assigned into the following five groups using simple randomization (n=12): i) The control group [sham operation + injection of the same volume of vehicle control (PBS) into knee joints]; ii) overexpression (OverExp)-XIST group control (sham operation + injection of overexpression-XIST plasmids into knee joints); iii) model group (OVX + injection of the same volume of control vehicle (PBS) into knee joints); iv) model + short hairpin (sh)RNA-negative control (NC) group (OVX + injection of shRNA-NC into knee joints); and v) model + shRNA-XIST group (OVX + injection of shRNA-XIST into knee joints).…”
Section: Methodsmentioning
confidence: 99%